Ribosomal DNA representation in the Orbach-Sachs and Vollmer-Yanofsky N. crassa cosmid libraries - K. Sylvester; D. O. Natvig (Fungal Genetics Reports, 1993)
We have been employing the Orbach-Sachs (1991 Fungal Genetics Newsl. 38:97) and Vollmer-Yanofsky (Vollmer and Yanofsky 1986 Proc. Natl. Acad. Sci. USA 83:4869-4873) N. crassa cosmid libraries (obtained from the Fungal Genetics Stock Center) in subtractive hybridization experiments designed to identify genes induced under conditions of oxidative stress. Because cosmids containing the 17S and 26S ribosomal RNA genes produce false positives in these experiments, it was necessary for us to identify cosmids in the Orbach-Sachs containing these genes.